Neurodegeneration in equine grass sickness is not attributable to niacin deficiency. (3rd October 2016) - McGorum, B. C.; Jago, R. C.; Cillan‐Garcia, E.; Pirie, R. S.; Keen, J. A.; Reardon, R. J. M.; Saffu, P. Y.; Miller, N. J.
Summary: Background: The aetiology of equine grass sickness (EGS) is currently unknown. We hypothesised that an acute deficiency of niacin (vitamin B3), which plays a key role in neural homeostasis, may contribute to neurodegeneration in EGS. Niacin deficiency can potentially result from ingestion of niacin antagonists produced by pasture mycotoxigenic fungi. Objectives: To compare the niacin status of EGS and control grazing horses. A secondary objective was to compare blood concentrations of vitamins B1, B2 and B6 in EGS and control grazing horses to determine if the status of these vitamins was altered in EGS. Study design: Case–control study. Methods: Indices of niacin status, namely the erythrocyte nicotinamide adenine dinucleotide:nicotinamide adenine dinucleotide phosphate ratio (NAD:NADP ratio) and erythrocyte concentrations of NAD and NADP, were compared in blood collected from EGS and healthy control grazing horses. Blood concentrations of vitamins B1, B2 and B6 were also compared. Results: There was no significant intergroup difference in the NAD:NADP ratio, the main index of functional niacin status (control group: median 2.1, interquartile range [IQR] 1.8–2.6; EGS group: median 2.1, IQR 1.9–2.6). EGS horses had significantly higher (median value increased by 25%) concentrations of NADP. There were no intergroup differences in blood concentrations of vitamins B1, B2 and B6. Main limitations: The interpretation of data was limited by the lack of previously defined equine reference ranges for many of the analytes. Sample size was low. Conclusions: Niacin deficiency does not contribute to EGS neurodegeneration.